Vector optomechanical entanglement - Li Ying; Jiao Ya-Feng; Liu Jing-Xue; Miranowicz Adam; Zuo Yun-Lan; Kuang Le-Man; Jing Hui (Nanophotonics, 2021)
The polarizations of optical fields, besides field intensities, provide more degrees of freedom to manipulate coherent light–matter interactions. Here, we propose how to achieve a coherent switch of optomechanical entanglement in a polarized-light-driven cavity system. We show that by tuning the polarizations of the driving field, the effective optomechanical coupling can be well controlled and, as a result, quantum entanglement between the mechanical oscillator and the optical transverse electric mode can be coherently and reversibly switched to that between the same phonon mode and the optical transverse magnetic mode. This ability to switch optomechanical entanglement with such a vectorial device can be important for building a quantum network being capable of efficient quantum information interchanges between processing nodes and flying photons.